Researchers Remember Research as an Arena of Memory Among Descendants of Holocaust Survivors, a Collected Volume of Academic Autobiographies - Baumel-Schwartz, Judith Tydor; Baumel-Schwartz, Judith Tydor; Refael, Shmuel (Peter Lang, 2021)
The book Researchers Remember: Research as an Arena of Memory Among Descendants of Holocaust Survivors, a Collected Volume of Academic Auto-biographies is composed of over 30 essays written by prominent researchers worldwide belonging to the (3z(BSecond Generation(3y (Band (3z (BThird Generation(3y (Bof Holocaust offspring. Each essay traces the author$1 (Bs path to a research profession, focusing on the influence of their family$1 (Bs Holocaust background at various crossroads of their life.s